PENGARUH PEMBERIAN EKSTRAK ETANOL RIMPANG LENGKUAS (ALPINIA GALANGA) TERHADAP GAMBARAN HISTOPATOLOGI OTAK MENCIT (MUS MUSCULUS L) YANG DIINDUKSI MONOSODIUM GLUTAMATE - Emeraldha Theodorus; Muhartono Muhartono; Giska Tri Putri (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2019)
Abstract Background: Monosodium glutamate (MSG) induced brain damage characterized by microscopic neuronal necrosis and clinically neurologic deficits. Galangal has flavonoid that serves as an antioxidant that can protect the brain. Objective: To determine the effect of ethanol extract of galangal rhizome (Alpinia galanga) on brain histopathological appearance in the mice (Mus musculus L) induced by Monosodium glutamate (MSG). Methods: This study used 30 mice that were divided into 5 groups. K(-) is not given any treatment, K(+) is given intraperitoneal MSG 4 mg/grBB, P1 is given intraperitoneal MSG 4 mg/grBB and oral galangal extract 14 mg/ 20grBB, P2 is given intraperitoneal MSG 4 mg/grBB and oral galangal extract 28 mg/ 20grBB, and P3 P1 is given intraperitoneal MSG 4 mg/grBB and oral galangal extract 56 mg/ 20grBB. Results: The average number of brain neuronal necrosis were K(-) 3,8; K(+) 5,4; P1 5,4; P2 5; dan P3 4,8. The One-Way ANOVA result showed that the p-value =……. 0,015. Conclusion: There are no difference in the effect of ethanol extract of galangal rhizome (Alpinia galanga) on brain histopathological appearance in the mice (Mus musculus L) induced by Monosodium glutamate (MSG).